Hubungan antara Dukungan Sosial Teman dengan Resiliensi pada Korban Revenge Porn di Media Sosial - Putri, Aisyah Nadia; Dwatra, Free Dirga (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to determine the relationship between friends’ social support and resilience in revenge porn victims in social media. The research type used in this research is quantitative research. The sample collecting technique used in this research is purposive sampling with revenge porn victims as the population. The subject’s criterias are people above 17 years old, not living with parents, have experienced stress, anxiety, depression, have had thinking about ending their lives, or even received any psychological treatments from the professionals due to the revenge porn they have faced. The subject obtained were 50 people. This research uses a questionnaire with friends’ social support scale and resilience scale both with 0,968 and 0,852 worth or reliability. The data analysis technique used was Product Moment Correlation with r=0,457 and P0,001 obtained as results, which means there is a significant positive correlation between the two variables. The result of this research is that H1 is accepted, whicvh means there is a significant positive relationship between friends’ social support and resilience among revenge porn victims on social media.